Constrained variational approach for energy derivatives in Intermediate hamiltonian fock-space coupled-cluster theory - Ghosh, Aryya; Gupta, Jitendra; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
Fock-space multi-reference coupled cluster theory is an efficient method for electronic structure of nearly degenerate cases. However, it suffers from the intruder state problem for large model space. The intermediate Hamiltonian formulation eliminates intruder state problem and helps in the convergence of equations. In this paper we have implemented intermediate Hamiltonian approach in Fock-space coupled cluster method for the response properties. We test our method for the dipole moments of doublet radicals. We report dipole moments of CN, SF and NS radicals. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Constrained variational approach; Fock-space multi-reference coupled cluster; Intermediate Hamiltonian theory; Response approach

CAP/EOM-CCSD method for the study of potential curves of resonant states - Ghosh, Aryya; Karne, Anagha S.; Pal, Sourav; Vaval, Nayana (Physical Chemistry Chemical Physics, 2013)
The equation-of-motion coupled-cluster (EOM-CC) method along with the complex absorbing potential (CAP) is used for the study of resonance in e(-)-N-2 and e(-)-CO. Resonance position and width are studied as a function of bond length. We report the potential curves (PC) of the resonance states.

Complex absorbing potential based equation-of-motion coupled cluster method for the potential energy curve of CO2- anion - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav; Bartlett, Rodney J. (Journal of Chemical Physics, 2014)
The equation-of-motion coupled cluster method employing the complex absorbing potential has been used to investigate the low energy electron scattering by CO2. We have studied the potential energy curve for the (2)Pi(u) resonance states of CO2- upon bending as well as symmetric and asymmetric stretching of the molecule. Specifically, we have stretched the C-O bond length from 1.1 angstrom to 1.5 angstrom and the bending angles are changed between 180 degrees and 132 degrees. Upon bending, the low energy (2)Pi(u) resonance state is split into two components, i.e., (2)A(1), B-2(1) due to the Renner-Teller effect, which behave differently as the molecule is bent. (c) 2014 AIP Publishing LLC.

Charge transfer effect on relaxation mechanism in hydrated pyrrole-water systems following N-2s ionization - Kumar, Ravi; Bhattacharjee, Kankana; Ghosh, Aryya; Vaval, Nayana (ChemPhysChem, 2025)
This study investigates the relaxation mechanisms of pyrrole and pyrrole-water clusters (C4H5N-(H2O)n, where n=0-3 \${n = 0 - 3}\$ ) following N-2s ionization of pyrrole. Using various theoretical methods, we focus on the influence of water molecules and charge transfer on these non-radiative relaxation pathways. Our simulations included pyrrole solvated in 494 explicit water molecules equilibrated at 300 K and also employed a polarizable continuum model (PCM) to make the system more realistic and gain additional insights. In hydrated environments, the hydrogen bonding network between pyrrole and surrounding water molecules facilitates enhanced non-radiative relaxation pathways following inner valence ionization. Since these are hydrogen bonding systems, we have explored the possibility of proton transfer, which could occur in conjunction with other electronic decay processes.
Keywords: ab initio-calculations; auger decay; charge transfer; proton transfer; pyrrole